Doubling Back on Double Marginalization - Laurent Linnemer (Center for Economic Studies and ifo Institute (CESifo), 2022)
"Double marginalization" and "Elimination of Double marginalization" are catch-phrases commonly used in the IO literature. In this note, I trace back the origin of the idea to Chapter IX, on complementary goods monopolies, of Cournot (1838). Through the years Cournot's contribution remained a reference but ended being viewed as a special case of the bilateral monopoly model. Yet, it is worth wondering why the most cited paper on this issue is nowadays Spengler (1950) which contains only an informal treatment of the question. In addition to retracing the origin of the idea, I emphasize the elegant proof of Cournot for the simultaneous game and extend it to the sequential game. I also show that prices are usually higher in the sequential game but that they could be lower if demand is very convex.
Keywords: B16; B21; K21; L12; L13; L42; 330; Cournot; complements; successive monopolies